Biomarkers of Cardiovascular Disease in Patients With Ankylosing Spondylitis - Ümit SARP,; Evren ÜSTÜNER,; Sehim KUTLAY,; Şebnem ATAMAN,; Sim KUTLAY, (Archives of Rheumatology, 2020)
Objectives: This study aims to evaluate the inflammatory status and clinical and vascular alterations using tonometry and B-mode sonography in patients with ankylosing spondylitis (AS). Patients and methods: The study included 71 AS patients (57 males, 14 females; mean age 40.1±10.8 years; range, 29 to 51 years) without cardiovascular disease and 30 healthy controls (24 males, 6 females; mean age 41.2±9.3 years; range, 32 to 50 years). We evaluated participants’ clinical, biological and functional status along with laboratory data and measured both the arterial stiffness using carotid-femoral pulse wave velocity (PWV) measured by applanation tonometry and carotid intima-media thickness (CIMT) as a preclinical atherosclerosis marker. Results: The mean disease duration of AS patients was 10.6±4.2 years. CIMT (p=0.03) and PWV (p=0.04) data showed significant differences between AS patients and healthy controls. Multiregression analysis showed that PWV correlated with age (r2=0.42; p=0.03) and disease duration (r2=0.31; p=0.04), while CIMT correlated with disease duration (r2=0.37; p=0.03) and Bath Ankylosing Spondylitis Disease Activity Index (r2=0.3; p=0.04). Conclusion: This study demonstrated an increase in early preclinical atherosclerosis in AS patients without cardiovascular (CV) disease compared to healthy controls. Therefore, screening AS patients with noninvasive methods for atherosclerosis and subclinical vasculopathy would allow us to take primary prevention measures. We found that the major determinant for increased CV risk was the disease duration, while there was no difference between different treatment modalities.